Are evolutionary transitions in sexual size dimorphism related to sex determination in reptiles?. (9th March 2021) - Katona, Gergely; Vági, Balázs; Végvári, Zsolt; Liker, András; Freckleton, Robert P.; Bókony, Veronika; Székely, Tamás
Abstract: Sex determination systems are highly variable in vertebrates, although neither the causes nor the implications of this diversity are fully understood. Theory suggests that sex determination is expected to relate to sexual size dimorphism, because environmental sex determination promotes sex‐specific developmental bias in embryonic growth rates. Furthermore, selection for larger size in one sex or the other has been proposed to drive the evolution of different genetic sex determination systems. Here, we investigate whether sex determination systems relate to adult sexual size dimorphism, using 250 species of reptiles (Squamata, Testudines and Crocodylia) representing 26 families. Using phylogenetically informed analyses, we find that sexual size dimorphism is associated with sex determination: species with TSDIa sex determination (i.e. in which the proportion of female offspring increases with incubation temperature) have more female‐biased size dimorphism than species with TSDII (i.e. species in which males are produced at mid temperatures). We also found a trend that species with TSD ancestors had more male‐biased size dimorphism in XY sex chromosome systems than in ZW sex chromosome systems. Taken together, our results support the prediction that sexual size dimorphism is linked to sex‐dependent developmental variations caused by environmental factors and also by sex chromosomes. Since the extent of size dimorphism is related to various behavioural, ecological and life‐history differences between sexes, our results imply profound impacts of sex determination systems for vertebrate diversity. Abstract : The phylogenetic distribution of sex determination systems (outer ring) and sexual size dimorphism (inner ring) in reptiles.